Desenvolvimento coparticipativo de um Plano Local Estratégico para a Demência – análise de uma proposta para um território do Centro de Portugal - Marlene Rosa; Susana Lopes; Raquel Sabino (Cidades, Comunidades e Território)
In this study, the co-participative development of a Local Strategic Plan for Dementia is presented and analysed. Fifteen institutions from a territory in central Portugal participated in this dynamic, each represented by a reference professional and 2 senior technicians from the City Council (n=17). Participants with previous experience in providing care to elderly people and caring for people with dementia were recruited. The co-participative ideation dynamics took place in a single 8-hour session, which was divided into 4 distinct phases: (i) icebreaker presentation, (ii) co-design of objectives, (iii) co-design of strategic axes, (iv) co-design of intervention. A content analysis of the exercises and a summary were carried out according to the following structure: objectives for the strategic plan, strategic axes and actions to be implemented. Throughout the ideation exercises, more significant keywords were defined, reflecting the most relevant dimensions in assistance and care for people with dementia: 10 dimensions for processes, 7 for social health, and 7 for policies. Five axes were defined: Community Literacy, Combating Isolation, Aging in Place, Intergenerational, and Dementia Friendly Service, which were supported by 13 objectives, 15 actions and 17 goals and 20 strategic partners. The design of a co-participative proposal for a Local Strategic Plan for Dementia proved to be an innovative and effective methodology, and it should, in the future, involve other community stakeholders and develop lines of action for the coordination and monitoring of the strategy.